Stem cells: immortality or a healthy old age? - McWhir, Jim (Henry Stewart Talks, 2007)
What is a stem cell?, Properties of stem cells, Adult and embryonic stem cells, What is immortality?, Why do we die?, Mechanisms of programmed cell death, Mutation, Connection between tumour protection and ageing, Impact of regenerative medicine, Impact of stem cells on lifespan, Average and maximum lifespan
Updated at 2009/08/25